(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
High frequency plant regeneration was established from shoot tips and nodal explants of a perennial ornamental plant, Dianthus caryophyllus L. Best shoot induction was observed on MS basal medium supplemented with 0.5 mg/l BAP + 0.1 mg/l NAA, in which 82% of the explants responded to produce maximum number of shoots (38) per culture. In vitro raised healthy shoots were rooted on half strength MS medium with 0.5 mg/l IBA +0.5 mg/l NAA. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for 7 days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 78%. Key words: Dianthus caryophyllus; Shoot proliferation; Micropropagation; Acclimatization DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9597 BJSIR 2011; 46(4): 495-498